Strengthening MSME Digital Literacy through the HALVORA Platform - Dimas Bagus Wiranatakusuma; Fawwaz Ardhan Kencana; Satria Utama (Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital literacy has emerged as a foundational determinant of MSME participation in digital platform economies, yet its conceptualization and measurement remain inconsistent across the literature. This study conducts a Systematic Literature Review (SLR) of 20 Scopus-indexed articles to examine how digital literacy interventions shape MSME outcomes within platform ecosystems, with particular reference to the HALVORA digital empowerment platform deployed in Sleman Regency, Yogyakarta. Guided by the PRISMA methodology and analyzed through VOSviewer bibliometric mapping, the study identifies five thematic clusters: customer satisfaction and AI-driven commerce; information systems and management frameworks; fintech and vertical marketplace applications; competitive market structures; and blockchain-based financial infrastructure. The density visualization confirms commerce and information systems as the most intensively studied research anchors, while the overlay visualization reveals that blockchain, data marketplaces, and financial assets are the most rapidly emerging themes (2024–2025). Field survey data collected from MSME participants in Sleman show that 83.8% demonstrate high literacy and openness toward educational marketplace platforms, with 87.7% affirming the value of integrated digital marketing as a business capability. The findings underscore that effective digital literacy programs must address platform competency, digital payment skills, and marketing analytics simultaneously. This study recommends the HALVORA platform as a scalable vehicle for context-sensitive digital literacy enhancement, with training design grounded in the community's specific marketplace engagement patterns and business sector needs.